Implications of free Shiga toxin-converting bacteriophages occurring outside bacteria for the evolution and the detection of Shiga toxin-producing Escherichia coli - Martínez-Castillo, Alexandre; Muniesa, Maite (Frontiers in Cellular and Infection Microbiology, 2014)
In this review we highlight recent work that has increased our understanding of the distribution of Shiga toxin-converting phages that can be detected as free phage particles, independently of Shiga toxin-producing bacteria (STEC). Stx phages are a quite diverse group of temperate phages that can be found in their prophage state inserted within the STEC chromosome, but can also be found as phages released from the cell after activation of their lytic cycle. They have been detected in extraintestinal environments such as water polluted with feces from humans or animals, food samples or even in stool samples of healthy individuals. The high persistence of phages to several inactivation conditions makes them suitable candidates for the successful mobilization of stx genes, possibly resulting in the genes reaching a new bacterial genomic background by means of transduction, where ultimately they may be expressed, leading to Stx production. Besides the obvious fact that Stx phages circulating between bacteria can be, and probably are, involved in the emergence of new STEC strains, we review here other possible ways in which free Stx phages could interfere with the detection of STEC in a given sample by current laboratory methods and how to avoid such interference.